Coagulopathy, injury severity and bleeding progression but not prior antiplatelet and anticoagulation therapies drive prognosis in patients with moderate to severe traumatic brain injury - Lieschke, Franziska; Marggrander, Daniel T.; Kohlhase, Konstantin D.; Touma, Daniel; Schaefer, Jan Hendrik; Reitz, Sarah C.; Konczalla, Juergen; Schindler, Cora R.; Grefkes, Christian; Bohmann, Ferdinand O. (Frontiers in Neurology, 2025)
IntroductionAntiplatelet and anticoagulant therapies complicate the management and outcomes of traumatic brain injury (TBI) patients. This study evaluates clinical profiles and short-term outcomes focusing on prior antihemostatic therapy and tranexamic acid (TXA) use.Patients and methodsWe analyzed TBI patients admitted to University Hospital Frankfurt (2018–2021), assessing demographics, injury characteristics, clinical course, and short-term outcomes. The primary endpoint was hemorrhage progression; secondary endpoints included the modified Rankin Scale (mRS) at discharge, mortality and thromboembolic complications. Regression models identified predictors of functional outcome and mortality.ResultsAmong 218 patients (median age 70 years, 35% female, median GCS at admission 7), 44% had prior antiplatelet or anticoagulation therapy. These patients were older, had higher pre-injury mRS scores, and more often sustained TBIs from falls. While hemorrhage progression was similar, they had worse mRS scores (p = 0.02) and higher mortality (p = 0.002). Coagulopathy (OR 1.11, CI 1.07–1.16, p < 0.001), injury severity (OR 2.25, CI 1.51–3.41, p < 0.001), and bleeding progression (OR 2.23, CI 1.48–3.41, p < 0.001) predicted poor functional outcomes. TXA was more often given to younger, severely injured patients but did not impact outcome.ConclusionThis study underscores the need for tailored therapeutic approaches to improve survival and functional recovery in patients with pre-injury antiplatelet and anticoagulant therapies.